AUTOMATED PART DECOMPOSITION FOR PRODUCT ARCHITECTURE MODELING. (May 2020) - Redeker, J.; Gebhardt, P.; Reichler, A.-K.; Türck, E.; Dröder, K.; Vietor, T.
Abstract: This paper presents an algorithm that contributes to an automatic decomposition of a mechanical part based on geometric features and methods of unsupervised machine learning. For the development of the algorithm, existing techniques of 3D shape segmentation, especially surface-based part segmentation procedures are reviewed and important areas of activities are revealed. The developed multi-step approach results in an abstract product model. This representation leads to a new way of designing and redesigning parts for the novel hybrid manufacturing concept Incremental Manufacturing (IM).